Bilateral pulmonary embolism in a patient with pulmonary tuberculosis: a rare association in Yaoundé, Cameroon - Ekukwe, Nkoke Clovis (The African Field Epidemiology Network, 2014)
Pulmonary embolism is a complication of pulmonary tuberculosis that has received little emphasis in the literature. We describe a 52 year old male, with no risk factors for thromboembolic disease referred to our service for an in depth clinical review for cardiomegaly and dyspnea on exertion. Echocardiography and CT scans revealed dilated heart cavities and bilateral proximal pulmonary emboli respectively and a cavitation in the apical lobe of the right lung. Bronchial aspirate and culture revealed the presence of mycobacterium tuberculosis. There was no evidence of malignancy. Elsewhere, a clinical review and a lower limb ultrasound showed no evidence of deep venous thrombosis. Clinical course on anti - tuberculosis and anti - coagulant therapies was remarkably favorable. Clinicians need to be conscious of the risk of developing thromboembolic disease in patients treated for tuberculosis, in especially high prevalence settings like ours.